Fusarium wilts of ornamental crops and their management. (July 2015) - Gullino, M. Lodovica; Daughtrey, Margery L.; Garibaldi, Angelo; Elmer, Wade H.
Abstract: The production of ornamental plants continues to be a thriving and expanding industry in the United States, Canada, South America, Australia, and Europe, supported by plant industries in many developing countries. Fusarium wilt diseases, however, continue to plague the industry due to imperfections in clean stock propagation systems, latency of disease development, irrigation systems that allow propagule spread, and a low priority placed on breeding efforts towards Fusarium-resistant cultivars of ornamentals. Management requires a multifaceted approach employing cultivar resistance as well as cultural, biological, and chemical strategies. Ignorance of the sources of inoculum and how it is spread has allowed many missed opportunities for preventing Fusarium wilt diseases. When the disease has become established in a production system, many approaches for achieving suppression have been explored, but most have not met the high standard for a zero disease threshold demanded by the industry. The following review was designed to highlight management studies that have advanced our knowledge of how to minimize Fusarium diseases and to indicate areas where additional research and technological development are needed.